2013
DOI: 10.1080/02640414.2013.849000
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb joint kinetics during the first stance phase in athletics sprinting: three elite athlete case studies

Abstract: Abstract:This study analysed the first stance phase joint kinetics of three elite sprinters to improve the understanding of technique and investigate how individual differences in technique could influence the resulting levels of performance. Force (1000 Hz) and video (200 Hz) data were collected and resultant moments, power and work at the stance leg metatarsal-phalangeal, ankle, knee and hip joints were calculated. The metatarsal-phalangeal and ankle joints both exhibited resultant plantarflexor moments thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 37 publications
10
64
0
Order By: Relevance
“…Thus, the present findings do not support the notion that back-side mechanics should be minimised, at least in this group of sprinters. Bezodis et al 5,6 assessed the first step out of the blocks in well-trained sprinters and observed that greater hip extension was associated with higher levels of external power production. Optimal extension in the stance hip joint at lift-off during acceleration is likely important for at least two reasons: i) to ensure maximal utilisation of the hamstrings and glutes and ii) to orient the ground reaction forces more horizontally, particularly when combined with a simultaneous and sufficient knee lift for the swing leg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present findings do not support the notion that back-side mechanics should be minimised, at least in this group of sprinters. Bezodis et al 5,6 assessed the first step out of the blocks in well-trained sprinters and observed that greater hip extension was associated with higher levels of external power production. Optimal extension in the stance hip joint at lift-off during acceleration is likely important for at least two reasons: i) to ensure maximal utilisation of the hamstrings and glutes and ii) to orient the ground reaction forces more horizontally, particularly when combined with a simultaneous and sufficient knee lift for the swing leg.…”
Section: Discussionmentioning
confidence: 99%
“…The fastest runners maximize their acceleration and maximum sprinting velocities by applying greater mass-specific ground forces, [1][2][3] but research literature has so far provided limited information regarding how sprinting athletes should optimize their movements. Due to technology limitations, experimental kinematic studies have typically focused on the measurement area either around the start, [4][5][6] the acceleration phase [7][8][9][10] or during the maximal velocity phase, [11][12][13] typically assessing 1-3 steps. Only a few scientific studies have investigated the kinematics of athletic sprinting based on high-resolution assessments of >6 steps.…”
Section: Introductionmentioning
confidence: 99%
“…Power was calculated by multiplying the moment by the joint angular velocity; positive power indicated that mechanical energy was being generated, whereas negative power indicated energy absorption (White & Winter, 1985). The amount of work done at each joint was calculated as the time integral of the power curve using the trapezoidal rule (Bezodis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed an optimal cut-off frequency ranging from 47 -52 Hz in all three force directions, so 50 Hz was chosen as the cut-off frequency. However, because errors have been found to occur during initial contact in similar movements such as sprinting (Bezodis, Salo, & Trewartha, 2014), the first 60 ms of the GRF data were filtered at 10 Hz to match the low cut-off frequencies of the kinematic data and therefore minimise inaccuracies during impact (Bisseling & Hof, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…planting the stance foot more posterior relative to the centre of mass (CM) at touchdown, facilitated a forward leaning position and the generation of greater horizontal propulsive forces. The knee joint has been linked to forward lean during the first stance phase (Debaere, Delecluse, Aerenhouts, Hagman, & Jonkers, 2013) and knee extensor moments and powers have recently been identified as an important feature of the first stance phase in well-trained and international-level sprinters (Bezodis, Salo, & Trewartha, 2014;Charalambous, Irwin, Bezodis, & Kerwin, 2012;Debaere et al, 2013). It is therefore possible that any effects of touchdown distance on early acceleration performance are related to knee joint mechanics at touchdown.…”
Section: Introductionmentioning
confidence: 97%